2018
DOI: 10.1111/trf.14907
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of severe refractory autoimmune hemolytic anemia after hematopoietic stem cell transplant with abatacept

Abstract: Abatacept may provide significant clinical benefit in the management of AIHA after HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The next line of treatment he received was abatacept, a fusion protein composed of the Fc region of the immunoglobulin IgG1 fused to the extracellular domain of cytotoxic T‐lymphocyte antigen‐4, which inhibits T‐cell costimulation by binding to CD80/CD86 on antigen‐presenting cells . Starting on day +230, four doses of abatacept (10 mg/m 2 ) once every 2 weeks were given, and showed no therapeutic effect.…”
Section: Case Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The next line of treatment he received was abatacept, a fusion protein composed of the Fc region of the immunoglobulin IgG1 fused to the extracellular domain of cytotoxic T‐lymphocyte antigen‐4, which inhibits T‐cell costimulation by binding to CD80/CD86 on antigen‐presenting cells . Starting on day +230, four doses of abatacept (10 mg/m 2 ) once every 2 weeks were given, and showed no therapeutic effect.…”
Section: Case Descriptionmentioning
confidence: 99%
“…9 The child was transplanted with a peripheral blood stem cell (PBSC) collected graft inhibits T-cell costimulation by binding to CD80/CD86 on antigenpresenting cells. 12 Starting on day +230, four doses of abatacept (10 mg/m 2 ) once every 2 weeks were given, and showed no therapeutic effect. On day +254, a pulse of high-dose solumedrol (3 days of 10 mg/kg/day) was given, followed by a second course of rituximab, again without any improvement.…”
Section: Case Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that BOS is explicitly characterized by disturbance of B cell homeostasis with increased CD19 + CD21 -B cells and excess of B cell activation factor (BAFF) [38], abatacept might target Tfh cells in this context, which would at least partially explain the particular improvement of patients with BOS in our study. In addition, we observed a complete response in a steroid and rituximab refractory AIHA patient as previously described [39]. Despite not meeting NIH diagnostic criteria for cGvHD, we included this patient in our analysis since it has recently been reported that based on biomarker profiles, patients with signs of immune mediated damage not diagnostic for cGvHD do not significantly differ from those showing diagnostic signs of cGvHD suggesting that the current NIH diagnostic criteria may not involve all targets of cGvHD [40,41].…”
Section: Discussionmentioning
confidence: 72%
“…Finally, a recent study showed the efficacy of the T-cell inhibitor abatacept in 3 post-allo-HSCT AIHA cases 50. Abatacept is a fusion protein formed by linking extracellular domain of cytotoxic T-lymphocyte antigen 4 with the Fc region of immunoglobulin G (IgG) and inhibits T-cell activation through competitive binding of CD80 and CD86 on antigen-presenting cells, thus blocking the required CD28 costimulatory interaction.…”
Section: Emerging Treatments For Post-allo-hsct Aihamentioning
confidence: 99%